GUIDE TO INDEX SUPPORTED HISTORICAL CUMULATIVE EMISSION PER CAPITA - Andra., Pro.David Andra. (International Journal of Multidisciplinary Research and Studies, 2021)
This paper uses the Lorenz curve and Gini index with adjustment to per capita historical cumulative emission to construct the carbon Gini index to live inequality in global climate change areas. The analysis shows that 70% of carbon space within the atmosphere has been used for an unequal distribution, which is sort of identical to that of incomes during a country with the largest gap between the rich and therefore the poor within the world. Carbon equity should be an urgency and priority within the climate agenda.